2018
DOI: 10.1371/journal.pone.0191028
|View full text |Cite
|
Sign up to set email alerts
|

Medication discrepancies across multiple care transitions: A retrospective longitudinal cohort study in Italy

Abstract: PurposeMedication discrepancies are defined as unexplained differences among regimens across different sites of care. The problem of medication discrepancies that occur during the entire care pathway from hospital admission to a local care setting discharge (namely all types of settings dedicated to formal care other than hospitals) has received little attention in the medical literature.The present study aims to (1) determine the prevalence of medication discrepancies that occur during the entire care pathway… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 34 publications
1
19
0
1
Order By: Relevance
“…In total, 14 studies reported data concerning the frequency of UMDs [49,50,57,59,60,66,70,74,83,84,88,93,95,98]. Three studies [83,84,93] used an established UMD definition, seven [49,50,59,60,70,74,95] developed their own and four [57,66,88,98] did not report any definition.…”
Section: Unintentional Medication Discrepancy Studiesmentioning
confidence: 99%
“…In total, 14 studies reported data concerning the frequency of UMDs [49,50,57,59,60,66,70,74,83,84,88,93,95,98]. Three studies [83,84,93] used an established UMD definition, seven [49,50,59,60,70,74,95] developed their own and four [57,66,88,98] did not report any definition.…”
Section: Unintentional Medication Discrepancy Studiesmentioning
confidence: 99%
“…Most studies on the prevalence of drug discrepancies have been conducted in adult populations, usually focusing on a transition point in care [7,19,20]. However, a few similar studies in children have been reported [21][22][23].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, "lack of documentation" was defined as any situation in which there was no trace of clinical documentation. As the "lack of a documentation" did not allow to assess the presence or absence of discrepancies, we evaluated the possible hypothesis of "lack of documentation" was considered to be a discrepancy with the aim of considering the worst possible scenario [7].…”
Section: Evaluation Of Discrepanciesmentioning
confidence: 99%
See 1 more Smart Citation
“…Wszystko to stanowić może element kontynuacji procesu koncyliacji lekowej. Sensowność tego typu współpracy na linii personel medyczny szpitala -farmaceuta w aptece ogólnodostępnej została poparta licznymi badaniami [14][15][16].…”
Section: Dyskusjaunclassified